2023
DOI: 10.1007/s13197-023-05778-0
|View full text |Cite
|
Sign up to set email alerts
|

Microbial investigation of cleanability of different plastic and metal surfaces used by the food industry

Abstract: Different conveyor belt materials used by the meat and other food industries were compared, regarding their cleanability as bacterial reduction rates in relation to their surface topography. Eleven thermoplastic polymers, four stainless steels, and five aluminized nanostructured surfaces were investigated under laboratory conditions. Cleanings were conducted with water only, and with an alkaline foam detergent. Overall, scanning electron microscopy revealed remarkable differences in the surface topography of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…More recently, Jaroni et al (2023) observed higher STEC attachment to high-density polyethylene coupons (up to 5.6 log CFU/cm 2 ) compared to stainless steel (up to 4.3 log CFU/cm 2 ) [ 47 ]. Many factors affect the formation and adhesion strength of biofilms in abiotic surfaces, such as electrostatic charges, surface tension and hydrophobicity, coating, roughness or fissure depth, and porosity [ 67 , 68 , 69 , 70 ]. The plastic surfaces used in this study had a high hydrophobicity and a rougher surface than the stainless steel.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Jaroni et al (2023) observed higher STEC attachment to high-density polyethylene coupons (up to 5.6 log CFU/cm 2 ) compared to stainless steel (up to 4.3 log CFU/cm 2 ) [ 47 ]. Many factors affect the formation and adhesion strength of biofilms in abiotic surfaces, such as electrostatic charges, surface tension and hydrophobicity, coating, roughness or fissure depth, and porosity [ 67 , 68 , 69 , 70 ]. The plastic surfaces used in this study had a high hydrophobicity and a rougher surface than the stainless steel.…”
Section: Discussionmentioning
confidence: 99%